KADAR LEMAK DAN PROFIL ASAM LEMAK JENUH, ASAM LEMAK TAK JENUH DAGING AYAM BROILER DENGAN PEMBERIAN PAKAN MENGANDUNG TEPUNG DAUN KAYAMBANG (Salvinia molesta) - T. Setiawati, T. Setiawati; U. Atmomarsono, U. Atmomarsono; B. Dwiloka, B. Dwiloka (Jurnal Teknologi Hasil Pertanian, 2016)
This study was aimed to determined fat content and saturated fatty acid profile (SFA), unsaturated fattyacid profil (PUFA and MUFA) broiler chicken meat feeding with kayambang leaf flour (Salvinia molesta). Thisresearch used 100 broiler chickens at 15 days old unsex with average weight 500 ± 6,99 g. This research usedCompletely Randomized Design. Ration treatments arranged for starter and finisher periods. Ration treatmentswere T0 (ration without Salvinia molesta leaf meal); T1 (ration with Salvinia molesta leaf meal 6%); T2 (rationwith Salvinia molesta leaf meal 12%); and T3 (ration with Salvinia molesta leaf meal 18%). The fat contentdata obtained were analyzed using Analysis of Variance at significance level of 5%. The fatty acid profile datawere analyzed using descriptive quantitative analysis. The results showed that Salvinia molesta leaf mealtreatment in broiler diet didn’t affect significantly (P <0.05) of fat content of the meat. Fatty acid profile showedamount of saturated fatty acids decreased from T0 to T3 of the amount of saturated fatty acids 53.21% to24.57% and the amount of unsaturated fatty acids increased from 39.94% to 68.79% from T0 to T3. Based onthe results of the present study it was concluded that Salvinia molesta leaf meal can to reduce the content ofsaturated fatty acid and increasing the content of unsaturated fatty acid.Keywords: broiler chicken, Salvinia molesta, saturated fatty acid, unsaturated fatty acid